2018
DOI: 10.1111/jir.12551
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Clinical Outcome Routine Evaluation‐Learning Disabilities 30‐Item (CORE‐LD30)

Abstract: Background There is paucity in availability of valid and reliable measures of psychopathology that can be routinely applied with an intellectual disability (ID) population in clinical practice. The psychometric properties of the Clinical Outcome Routine Evaluation-Learning Disabilities 30-Item version (CORE-LD30) are examined. Method The CORE-LD30 was administered to 271 sequential referrals to three National Health Service (NHS) ID services providing psychological support. A principal components analysis with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…Posttreatment clients demonstrated significant reductions on the Impact of Event Scale Intellectual Disabilities (Hall et al 2014) with medium effect sizes found ( d = .50). Small nonsignificant reductions were also found on the Clinical Outcome Routine Evaluation-Learning Disabilities (CORE-LD; Barrowcliff et al, 2018) ( d = .43) and the LANTS ( d = .46). Qualitative data also indicated that participants felt that they were listened to on group, and the group format was appropriate in facilitating therapeutic change.…”
Section: Resultsmentioning
confidence: 96%
“…Posttreatment clients demonstrated significant reductions on the Impact of Event Scale Intellectual Disabilities (Hall et al 2014) with medium effect sizes found ( d = .50). Small nonsignificant reductions were also found on the Clinical Outcome Routine Evaluation-Learning Disabilities (CORE-LD; Barrowcliff et al, 2018) ( d = .43) and the LANTS ( d = .46). Qualitative data also indicated that participants felt that they were listened to on group, and the group format was appropriate in facilitating therapeutic change.…”
Section: Resultsmentioning
confidence: 96%
“…whether the client’s level of distress has changed, and by how much). The CORE ID is recommended as a useful broad-ranging measure of psychopathology for use with people with intellectual disabilities (Barrowcliff et al , 2018; Briscoe et al , 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Many things not in that list have been achieved: the very widely used CORE-10 ( Barkham et al, 2013) joined the short forms aimed at sessional use. The LD-CORE-15 (Barton et al, 2008;Brooks et al, 2013) and LD-CORE-30 (Barrowcliff et al, 2018;Marshall & Willoughby-Booth, 2007) were added for people with mild to moderate learning difficulties and the 10-item YP-CORE (Twigg et al, 2009(Twigg et al, , 2016 for adolescents. A 14-item derived form was developed for use with non-help-seeking populations (GP-CORE, Sinclair et al, 2005).…”
Section: The Core System and Practice Based Evidencementioning
confidence: 99%
“…Hay muchos elementos de esa lista que se han conseguido: el ampliamente utilizado CORE-10 ( Barkham et al, 2013) se sumó a los formularios a utilizar en el curso de la sesión. Se añadieron LD-CORE-15 (Barton et al, 2008;Brooks et al, 2013) y LD-CORE-30 (Barrowcliff et al, 2018;Marshall & Willoughby-Booth, 2007) para personas con dificultades de aprendizaje leves a moderadas, y el YP-CORE de 10 ítems (Twigg et al, 2009(Twigg et al, , 2016 para adolescentes. Se desarrolló un formulario de 14 ítems para utilizar con poblaciones que no solicitaban ayuda (GP-CORE, Sinclair et al, 2005).…”
Section: El Sistema Core Y La Evidencia Basada En La Prácticaunclassified